Balloon recanalisation of a chronically occluded left internal mammary artery graft. Issue 2 (August 1993) - Mehan, V K; Meier, B; Urban, P
Abstract : A patient in whom balloon recanalisation of a chronically occluded left internal mammary artery graft was successful is described. A Magnum-Magnarail system was used, and a four month follow up showed no restenosis.